Gustav Born: pioneer in imaging platelet and leukocyte biology. (17th November 2018) - Cleary, Simon J.; Page, Clive P.
Abstract: Gustav Born achieved scientific fame for his application of light transmission aggregometry to the study of platelet function, but also led interdisciplinary research teams in pioneering quantitative in vivo imaging studies of platelet aggregation and leukocyte adhesion, and in conducting the first research into the biomechanical factors underlying atherosclerotic plaque rupture. Gus Born also communicated both current research findings and an integrated understanding of cardiovascular biology to a wide audience through acting as scientific advisor on several television productions. Using footage from two of these films, we discuss Gustav Born's scientific achievements and legacy.